Aplikasi Low Pass RC Filter Untuk Mengurangi Harmonisa Pada Lampu Hemat Energi - Wahri Sunanda; Rika Favoria Gusa (Universitas Syiah Kuala, 2012)
Voltage and current harmonics produced by nonlinear loads which reduce electrical power quality and energy saving lamp is one of example of it. This research was done by performing studies in harmonic voltage and harmonic current from four different brands of energy saving lamp having power rating of 8 watt, 16 watt, and 20 watt and uses IEEE Standard of 519-1992 as a reference in determining maximum limitation voltage and current harmonics. The result of the tests were showed that total harmonic distortion (THD) voltage at each different brand of energy saving lamp having power rating of 8 watt, 16 watt, and 20 watt did not exceed the IEEE 519-1992 maximum limitation of 5%. While total harmonic distortion (THD) current at each different brand of energy saving lamp having power rating of 8 watt, 16 watt, and 20 watt had exceed result range exceeding 71,2%. After using low pass RC filter as passive electronic circuit, the total harmonic distortion (THD) current was obtained for each different brand of energy saving lamp having power rating of 8 watt, 16 watt, and 20 watt, it was showed that the range of total harmonic distortion (THD) current under 14,262%.